The Behaviour of Reinforced Concrete Beams with Lap Splices Using Headed Bars (International Journal of Innovative Research in Engineering & Management, 2022)
The current study investigates the  behaviour of headed bar lap splices in reinforced concrete  beam tension zones. The effect of many variables  affecting the behaviour of flexural members with lap  splice in tension zone was examined. Using four point  loading, seven simply supported concrete beams were  tested until failure occurred. Beams used were having  same dimensions (220 x 250x 1600 mm), concrete  strength (25Mpa) and same longitudinal reinforcement  (µ= 0.616%).  It was discovered that the behaviour of an RCC beam can  be achieved in a spliced beam with a 100 percent cut off  ratio when the splice length is equal to 27 db without any  transverse reinforcement, or when the lap is equal to 15.5  db with transverse reinforcement. The analytical data  from the research further reveals that, by using transverse  reinforcement for the spliced zone, the mode of failure  changed from brittle to flexure. It was also discovered  that using the lap splice length specified by ACI 318-14  for headed bars without using confinement in the lap  splice zone resulted in brittle failure of beams and  reduced ductility.
Keywords: Tension zone; Beam; Bar; Lap splice; Load; Failure